Infectious origin of Alzheimer's disease: Amyloid beta as a component of brain antimicrobial immunity - Vojtechova, Iveta; Machacek, Tomas; Kristofikova, Zdenka; Stuchlik, Ales; Petrasek, Tomas (PLoS pathogens, 2022)
The amyloid cascade hypothesis, focusing on pathological proteins aggregation, has so far failed to uncover the root cause of Alzheimer's disease (AD), or to provide an effective therapy. This traditional paradigm essentially explains a mechanism involved in the development of sporadic AD rather than its cause. The failure of an overwhelming majority of clinical studies (99.6%) demonstrates that a breakthrough in therapy would be difficult if not impossible without understanding the etiology of AD. It becomes more and more apparent that the AD pathology might originate from brain infection. In this review, we discuss a potential role of bacteria, viruses, fungi, and eukaryotic parasites as triggers of AD pathology. We show evidence from the current literature that amyloid beta, traditionally viewed as pathological, actually acts as an antimicrobial peptide, protecting the brain against pathogens. However, in case of a prolonged or excessive activation of a senescent immune system, amyloid beta accumulation and aggregation becomes damaging and supports runaway neurodegenerative processes in AD. This is paralleled by the recent study by Alam and colleagues (2022) who showed that alpha-synuclein, the protein accumulating in synucleinopathies, also plays a critical physiological role in immune reactions and inflammation, showing an unforeseen link between the 2 unrelated classes of neurodegenerative disorders. The multiplication of the amyloid precursor protein gene, recently described by Lee and collegues (2018), and possible reactivation of human endogenous retroviruses by pathogens fits well into the same picture. We discuss these new findings from the viewpoint of the infection hypothesis of AD and offer suggestions for future research.
Keywords: Anti-Infective Agents; mozek; antibakteriální látky; Amyloid beta-Protein Precursor; Alzheimerova nemoc; Alzheimer Disease; Humans; lidé; antiinfekční látky; Anti-Bacterial Agents; Amyloid beta-Peptides; amyloidní beta-protein; amyloidový prekurzorový protein beta; Brain